Development of electrode for ionic thermocell - Yek, Kai Hau (Nanyang Technological University, 2023)
An ionic thermocell is an electrochemical device that converts heat into electrical energy by utilizing the thermoelectric effect in a thermogel electrolyte. The device consists of two electrodes, separated by a thermogel electrolyte, which is a temperature-responsive material that can change its ion conductivity and viscosity in response to changes in temperature. Voltage will be generated by ions migration in the thermogel electrolyte with temperature gradient. In recent years, ionic thermocells have attracted increasing attention as a promising alternative to traditional thermoelectric devices due to their low cost, scalability, and potential for waste heat recovery. This report aims to develop a potential electrode material that helps to better overcome the electrode/electrolyte interface to allow more redox reaction on the electrode surface and generate higher potential difference. This is done by fabricating and conducting conductivity test on shortlisted electrode materials. The performance of the electrodes in liquid electrolyte and thermogel electrolyte is also quantified via Seebeck coefficient measurement.